2018
DOI: 10.1590/0103-6440201802080
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to a Lithium Disilicate Glass Ceramic Etched with Hydrofluoric Acid at Distinct Concentrations

Abstract: This study evaluated the effect of different hydrofluoric acid (HF) concentrations on the bond strength between a lithium disilicate-based glass ceramic and a resin cement. Eighty ceramic-blocks (12×7×2 mm) of IPS e.Max CAD (Ivoclar Vivadent) were produced and randomly assigned to 8 groups, considering 2 study factors: HF concentration in 4 levels, i.e., 1% (HF1), 3% (HF3), 5% (HF5), and 10% (HF10), and storage in 2 levels, i.e., baseline (tests were performed 24 h after cementation), and aged (storage for 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 19 publications
3
15
0
2
Order By: Relevance
“…Most studies reported the importance of ceramic surface pretreatment with HF acid of 4.8 to 10% and application for 15 s to 60s which agrees with the present findings [4046, 64]. Recent scientific data determined no significant differences in SBS values regarding prolonged etching time from 20s to 120 s for feldspar and LiS2 ceramic [32, 34].…”
Section: Discussionsupporting
confidence: 89%
“…Most studies reported the importance of ceramic surface pretreatment with HF acid of 4.8 to 10% and application for 15 s to 60s which agrees with the present findings [4046, 64]. Recent scientific data determined no significant differences in SBS values regarding prolonged etching time from 20s to 120 s for feldspar and LiS2 ceramic [32, 34].…”
Section: Discussionsupporting
confidence: 89%
“…The specimens submitted to thermal cycling showed lower SBS values between ceramic and bonding material in relation to the 24 h. Thus, the second hypothesis was rejected. These findings are in agreement with the previous studies, which found significant differences in bond strength after thermal cycling (1,10,21). However, some studies have found no significant difference for bond strength after thermal cycling.…”
Section: Discussionsupporting
confidence: 93%
“…The strategies involve micromechanical and chemical pretreatments, implying that the restoration surface requires surface roughening for mechanical bonding and surface activation for chemical adhesion [38]. Roughness increases the surface area available for bonding, promoting micromechanical interlocking with the resin cement [39,40]. On the other hand, wettability of the surface is an important actor for the bonding of ceramics, regardless of the bonding mechanism used [33,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the surface free energy improves the wettability of the surface for resin bonding [33,43]. Furthermore, the surface roughness also affects wettability of the ceramic surface since an increase in surface area induces an increase in wettability [39,44].…”
Section: Discussionmentioning
confidence: 99%